The microbiological characteristics of Staphylococcus aureus isolated from patients with native valve infective endocarditis. Issue 1 (1st January 2019) - Kim, Chung-Jong; Song, Kyoung-Ho; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Eu Suk; Park, Kyoung Un; Kim, Nam Joong; Park, Kyung-Hwa; Kwak, Yee Gyung; Cheon, Shinhye; Jang, Hee-Chang; Kim, Young Keun; et al.
ABSTRACT: The microbiological characteristics of Staphylococcus aureus causing infective endocarditis (IE) have not been investigated thoroughly. We compared the characteristics of S. aureus isolates from patients with and without IE. Cases of S. aureus bacteremia (SAB) were collected from 10 hospitals over 7 years. Cases of native valve IE were matched with non-IE controls according to the following criteria: central-line-associated infection, community-acquired infection, methicillin susceptibility, and if possible, the primary site of infection. Genes coding virulence factors were analyzed using multiplex polymerase chain reactions. Fibrinogen and fibronectin-binding properties were assessed using in vitro binding assays. The fibronectin-binding protein A gene ( fnbpA ) was sequenced. Of 2, 365 cases of SAB, 92 had IE. After matching, 37 pairs of S. aureus isolates from the IE cases and non-IE controls were compared; fnbpA was detected in 91.9% of the IE isolates and 100% of the non-IE isolates ( p = 0.24). While the fibrinogen binding ratio was similar (1.07 ± 0.33 vs . 1.08 ± 0.26, p = 0.89), the fibronectin-binding ratio was significantly higher in the IE-group (1.31 ± 0.42 vs . 1.06 ± 0.31, p = 0.01). The proportions of major single-nucleotide polymorphisms in fnbpA were as follows: E652D (2.9% vs . 2.7%), H782Q (65.6% vs . 60.6%), and K786N (65.6% vs . 72.7%). The fibronectin-binding ratio was positively correlated with the number of SNPs present in IE cases ( p < 0.001) but not in the non-IE controls ( p = 0.124). Fibronectin-binding might play a key role in SAB IE. However, the degree of binding may be mediated by genetic variability between isolates.